Open Access Scholarly Publications as OER - Anderson, Terry (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
This article presents the rationale, common practices, challenges, and some personal anecdotes from a journal editor on the production, use, and re-use of peer-reviewed, scholarly articles as open educational resources (OER). The scholarly and professional discourse related to open educational resources has largely focused on open learning objects, courseware, and textbooks. However, especially in graduate education, articles published in scholarly journals are often a major component of the course content in formal education. In addition, open access journal articles are critical to expanding access to knowledge by scholars in the developing world and in fostering citizen science, by which everyone has access to the latest academic information and research results. In this article, I highlight some of the challenges, economic models, and evidence for quality of open access journal content and look at new affordances provided by the Net for enhanced functionality, access, and distribution. In the seventeen years since I graduated with a doctorate degree, the climate and acceptance of open access publishing has almost reversed itself. I recall a conversation with my PhD supervisor in which he argued that publishing online was not a viable option as the product would not have permanency, scholarly recognition, or the prestige of a paper publication. His comments reflect the confusion between online resources and those described as open access, but as well illustrate the change in academic acceptance and use of open access products during the past decade. The evolution from paper to online production and consumption is a disruptive technology in which much lower cost and increased accessibility of online work opens the product to a completely new group of potential users. In the case of OER these consumers are primarily students, but certainly access to scholars from all parts of the globe and the availability to support citizen science (Silvertown, 2009) should not be underestimated.